Urinary Tamm-Horsfall Protein and Citrate: A Case-Control Study of Inhibitors and Promoters of Calcium Stone Formation - Pourmand, Gholamreza; Nasseh, Hamidreza; Sarrafnejad, Abdolfattah; Mehrsai, Abdolrasoul; Hamidi Alamdari, Darioush; Nourijelyani, Keramat; Shekarpour, Leila (Urology Journal, 2009)
Introduction: This study aimed to compare urinary Tamm-Horsfall protein (THP), citrate, and other inhibitors and promoters of stone formation in calcium stone formers with those in healthy individuals. Materials and Methods: From January 2002 to June 2004, 100 calcium stone formers (mean age, 38.6 ± 10.3 years) who had at least 2 episodes of calcium stone formation were compared with 100 healthy individuals (mean age, 33.8 ± 9.7 years). Their 24-hour urine THP (using the sodium dodecyl sulfate polyacrylamide gel electrophoresis method), citrate, calcium, uric acid, oxalate, and magnesium values were measured and compared. Results: The mean 24-hour urine THP was 3.3 ± 8.1 mg in patients in the study group and 4.6 ± 19.2 mg in controls (P = 0.5). However, THP in individuals with and without bacteriuria was significantly different (15.8 ± 33.6 versus 2.6 ± 10.2, P < 0.001). Mean 24-hour urinary calcium, citrate, and oxalate values were 232.6 ± 95.3 mg and 177.8 ± 82.7 mg (P < 0.001), 132 ± 103.2 mg and 395 ± 258.5 mg (P < 0.001), and 18.9 ± 22.5 mg and 10.4 ± 8.5 mg (P < 0.001) in patients in the study and control groups, respectively. There was a significant positive correlation between urinary citrate and promoters of stone formation, including urinary calcium, oxalate, and uric acid, in patients in the control group, but not in patients in the study group. Conclusion: THP in the urine of stone formers is not quantitatively different from that of healthy individuals, but it is different in patients with bacteriuria. Increased urinary excretion of calcium, oxalate, and uric acid in stone formers with no increase in urine citrate may play a role in the pathogenesis of recurrent stone formation.